Artemis Fowl: The Lost Colony - Colfer, Eoin.; Parker, Nathaniel (New York : Listening Library, 2006)
When demons begin appearing on Earth unpredictably, foreshadowing a cataclysmic breakdown of their magic, Artemis and his friends face a new foe--a twelve-year-old girl whose intellect just might match Artemis's own--as they try to prevent a catastrophe.
aUnabridged.
aCompact discs.
Read by Nathaniel Parker.
Keywords: Children's audiobooks; Adventure and adventurers -- Fiction; Space and time -- Fiction; Fairies -- Fiction; Magic -- Fiction; Demonology -- Fiction; Audiobooks